Corporate Social Responsibility and CEO Pay Performance Sensitivity: Evidence from Chinese listed firms - Song, Siwen; Ma, S.; Jun, A. (2019)
This study examines the impact of CSR on CEO pay performance sensitivity of Chinese listed firms from 2008 to 2016. Our results reveal that CSR performance as well as CSR report disclosure could increase CEO pay performance sensitivity. We find that the increased monitoring towards CEO power is the channel through which CSR impacts on CEO pay performance sensitivity by showing that the positive impact is more profound among SOEs, firms with CEOs taking dual roles and CEOs having political connections. We further show that mandatory feature itself does not contribute to the impact of CSR on CEO pay performance sensitivity in China. Our findings are obtained after controlling firm and year fixed effects, and further confirmed with Generalised Method of Moments IV (IV-GMM) estimation, as well as alternative instrumental variable and different measurement of key variables.